Застосування знижених ставок ПДВ на сільськогосподарську продукцію - Косторной, Сергій Володимирович; Косторной, Сергей Владимирович; Kostornoi, Serhii (Люкс, 2021)
UK: Державна підтримка аграрного сектору економіки через механізм оподаткування є поширеною практикою в розвинутих країнах. В статті систематизовано підходи до застосування знижених ставок ПДВ для сільськогосподарської продукції, продуктів харчування, сільськогосподарських ресурсів та послуг в країнах ЄС. Виконано порівняння відповідних українських законопроектів. Детально розглянуто сутність, переваги та недоліки законопроекту №3656, прийняття якого є найбільш імовірним. EN: The agricultural sector of the economy is of strategic importance for Ukraine and needs state support. Many countries around the world use preferential value added tax rates for agricultural or food products to provide such support. The aim of the article is to systematize the approaches to the implementation of reduced VAT rates on agricultural products, as well as to determine their possible impact on the financial performance of enterprises in the agricultural sector of the economy. The article discusses in detail the bill №3656, the adoption of which is the most likely.
Implementation of reduced VAT rates for agricultural products
Keywords: оподаткування; податок на додану вартість; ставки ПДВ; сільськогосподарська продукція; сільськогосподарські підприємства; taxation; value added tax; VAT rates; agricultural products; agricultural enterprises